Upaya Peningkatan Iklim Investasi Terhadap Peluang Kerjasama Investor Antar Daerah - Sukesi, Sukesi; Martha Hendrati, Ignatia (Jurnal Riset Ekonomi dan Bisnis, 2010)
Various attempts were made in order to attract regional investors. Both programs through licensing and incentive services performed. Nganjuk economic growth despite being below the economic growth in East Java Province level but, at the rate of economic growth in the District each year experience peningktan Nganjuk. Economic growth is one factor to look at the rate of local consideration of the local economy the way in offering or attract investors to invest their capital. In 2004 the value of investment in Nganjuk a sharp decline compared with previous years since 2000 until 2004 the value of investments decreased an average of 12.92% every year however, inversely proportional to the value of productivity. The value of productivity always increase from year to year with an average increase of 6.72%. Nganjuk always formulate increased investment because of, first to find out how the current investment climate, and how to analyze prospective investments for Nganjuk and prospective investment in associate with several other districts. Through case studies and comparative studies using analytical techniques approach the potential, problems and development investment; technical analysis of procedures and licensing; technical analysis of investment management, engineering analysis of the opportunities for inter-regional cooperation; and techniques are recommended including investment policy analysis to improve investment climate to become more conducive, it is necessary to: Create a regulation of direct investment and local investment, and established regional investment teams with the involvement of StakeholdersKeywords: Investment, Opportunity, Regional, Investment, Incentives